Educação ambiental, arte e tecnologia: ações educativas de aproveitamento de resíduos sólidos urbanos - Oliveira, Marilene Vilhena de (2007)
This thesis explores the application of concepts of Environmental Education, art and technology trough the practices developed in workshops with social groups in work situations at the university Universidade Tecnológica Federal do Paraná – UTFPR. The present research has the goal to enlarge the comprehension of the relationships between the Environmental Education and the way and the form to dispose the urban solid wastes. In the workshops it has been worked the notions and conceptions of Environmental Education, art and technology to give a different treatment to the solid wastes, as to separate material, to profit the aliments integrally and the application of art to transform these apparatus. Based on these ideas, the research was composed by the human being practices and reflections of the nature appropriation, and the industrial process and the socialization performances. The chosen methodology for the statistic and theoretical part of the thesis was receptively qualitative and quantitative. The workshops organization followed the research in action with five stages: the necessary material planning and providing; execution; work exposition; tasting; the research instruments application; and the draft of presents. The data were treated in software Excel. The thesis structure is divided in three main parts: the first was the theoretical fundaments; the second, the research in action, e the third, and the last, the analysis of the results. The conclusions finalized the text with the following connotations: the practices development for the Environmental Education actions can be done by the art and technology resources; the workshops made possible the socialization and the learning of values, behaviors and attitudes in relation to nature. Beyond, the education actions of the probably solid wastes generated in the participants houses of the sample a constructive repercussion, in the measure that the knowledge were being built and passed spontaneously to family and friends.